Prospects of foliar treatments with glycine solution to increase the productivity of dill - P. V. Pochuev; E. L. Malankina; L. N. Kozlovskaya (Овощи России, 2021)
Relevance. Dill is a popular food and medicinal crop (Anethum graveolens L.) of the Celery family (Apiaceae). Seeds of dill are included in the 14th edition of the State Pharmacopoeia of the Russian Federation. However, this crop is characterized by a relatively low yield, which reduces the efficiency of its production. The use of environmentally friendly growth-regulating compounds can significantly increase the yield and improve its quality. As a growth-regulating, foliar treatment with a solution of the amino acid glycine was tested. The amino acid glycine is environmentally friendly and does not pose a danger to humans and animals. The aim of the work was to increase the productivity of garden dill using foliar treatments with glycine amino acid.Materials and methods. Dill varieties Gribovsky and Symphony were chosen as objects to study the effect of the foliar treatments with glycine. Sowing of seeds was carried out at an early date, which for the conditions of the Lipetsk region corresponds to the first decade of April, with a SZT-3.6 seeder with 15 cm row spacing. The seeding rate was 15 kg/ha, the seeding depth was 1-2 cm. were Treatment with glycine solution was achieved in plants rosette phase. The concentration of glycine was 25, 50 and 100 mg / l. The control plants were sprayed with distilled water. The crop was cut during the period of brown seeds on the central umbrella. The content of essential oil was determined by the 14th edition of the State Pharmacopoeia of the Russian Federation (method 1). The content of the main components was determined by gas chromatography.Results. As a result of the research, a positive effect of foliar treatments with glycine on both yield and the content of essential oil in the raw material of dill varieties Gribovsky and Symphony was revealed. As a result of treatments, regardless of concentration, the seeds yield and the yield of essential oil per unit area increased. The increase in the mass of 1000 pieces of fruits was not unambiguous. Based on the results obtained, the effective concentration of amino acid glycine is determined not only by the characteristics of the variety, but also by weather conditions, when, depending on the conditions during the processing period and prior to harvesting, different aspects of the drug's action appear. According to the results of observations for 2 years and an assessment by the sum of the indicators, the optimal concentration of glycine in most cases was 100 mg / l, at the same time, for the Symphony variety for two years, two-foliar treatment with low concentrations of glycine (10 mg / l rosette + 10 mg / l budding).